Management of Genetic Syndromes 2005
DOI: 10.1002/0471695998.mgs049
|View full text |Cite
|
Sign up to set email alerts
|

Turner Syndrome

Abstract: Turner syndrome affects 1/3000 females. The natural history of this sex chromosome aneuploidy is marked by problems in lymphatic development, skeletal development and growth, gonadal function, cardiac and renal malformations, and a number of specific cognitive findings. An increased risk for hypothyroidism, sensorineural hearing loss, hypertension, and other problems is recognized. Evaluation and management are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 89 publications
0
13
1
Order By: Relevance
“…Among the 53 Turner syndrome cases, standard monosomy, mosaicism, and structural rearrangement accounted for 34.0% (18 cases), 54.7% (29 cases) and 11.3% (six cases), respectively. Compared to the relative frequencies of Turner syndrome reported by Jacobs et al [21] and Sybert [22], standard monosomy and structural rearrangement were found in this study at a lower, and mosaicism at a higher, incidence, which might be due to the possibility of maternal cell contamination and the high sensitivity of detecting mosaicism by the in situ culture method. But other reports have found that mosaicism is common in Turner syndrome, ranging from 66.7% [23] to 90% of cases [24].…”
Section: Discussioncontrasting
confidence: 87%
“…Among the 53 Turner syndrome cases, standard monosomy, mosaicism, and structural rearrangement accounted for 34.0% (18 cases), 54.7% (29 cases) and 11.3% (six cases), respectively. Compared to the relative frequencies of Turner syndrome reported by Jacobs et al [21] and Sybert [22], standard monosomy and structural rearrangement were found in this study at a lower, and mosaicism at a higher, incidence, which might be due to the possibility of maternal cell contamination and the high sensitivity of detecting mosaicism by the in situ culture method. But other reports have found that mosaicism is common in Turner syndrome, ranging from 66.7% [23] to 90% of cases [24].…”
Section: Discussioncontrasting
confidence: 87%
“…Associated extracardiac anomalies are detected in the 15–28% of cases, in the setting of chromosomal anomalies, Mendelian disorders, and organ defects [Natowicz et al, ; Ferencz et al, ]. Several chromosome anomalies are known to be associated with HLHS, including monosomy X (Turner syndrome) [Natowicz et al, ; Mazzanti and Cacciari, ; Loscalzo et al, ; Sybert, ], terminal deletions 11q (Jacobsen syndrome) [Grossfeld et al, ] and 15q26 [Lalani et al, ], trisomy 18 and trisomy 13 [Natowicz et al, ; Ferencz et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Turner syndrome, also called monosomy X syndrome, is the most common sex chromosome disorder that occurs when only one X chromosome is present and all or part of the second sex chromosome (X or Y) is missing (19, 90); hence, this condition occurs only in female subjects. Turner syndrome is associated with short stature, gonadal dysgenesis, webbing of the neck, cardiac abnormalities, estrogen deficiency, osteoporosis and congenital lymphoedema (19, 83, 90). Gonadal dysgenesis generally refers to a condition characterized by defective development of gonads in female subjects, resulting in loss of ovarian function and lack of estrogen hormone.…”
Section: X‐linked Genetic Diseases and The Periodontiummentioning
confidence: 99%